Making sense of the 'is' of constitution - Zerbudis, Ezequiel Jorge (2021)
I consider a problem that arises in connection with (alleged) cases of coincident objects (such as a statue and the lump of clay it is made of) and that affects the two main accounts that have been given of such cases, namely, Pluralism (according to which statue and lump are distinct) and Monism (according to which they are one). The problem is that both views seem committed to accepting strained interpretations of some of the statements used to describe the situation. I consider Pickel´s arguments against the Pluralist´s strategy of interpreting ´is´ as expressing constitution in sentences such as ´The statue is the lump of clay´, and provide reasons for rejecting them-so as to vindicate, eventually, the Pluralist position.